EFEKTIVITAS HISAB HAKIKI TADQIQI SEBAGAI METODE PENENTUAN AWAL BULAN KAMARIAH TERHADAP IMKANURRUKYAT - Indah Amaliah; Mahyuddin Latuconsina (Universitas Islam Negeri Alauddin Makassar, 2021)
The calendar has become an important part of society, especially when it comes to matters of worship, it is necessary to have a definite calculation related to the provisions of the time which are closely related to the implementation of worship. One simple method is Hisab Hakiki, which is a method of reckoning in determining the beginning of the Lunar month. This method is one of the simplest methods in determining the beginning of the lunar month. The advancement of astronomy today allows anyone to determine the position of celestial bodies using science so that the determination of the beginning of the lunar month will be very easy to determine.This study aims to determine the effectiveness of the intrinsic reckoning method in determining the beginning of the lunar month. This research is a library research which is studied systematically and is relevant to the object that is the subject of the problem. In answering these problems, this study uses normative research and uses ephemeral data in its calculations.Keywords : Effectivity, Hisab Hakiki, Beginning of the Lunar Moon